Microbiological Characterization of Raw Cow’s Milk Sold in Zongo in the Commune of Cotonou - TCHEKESSI, C. K. Célestin; Sachi, S.A. Pivot; Kouglenou, Sylvain; Kintogandou, Marius; Tohoessou, A.E.E. Roland; Assogba, Karl; Banon, S.B. Jultesse; Bleoussi, T.M. Roseline; Djogbe, A.M. Anayce; AZOKPOTA, PAULIN; Bokossa, Yaou P. Innocent (My University, 2021)
Milk is a favorable environment for the growth of microorganisms. Thus, the microorganisms likely to be found in the milk can be at the base of several food poisonings. This work aims to assess the microbiological quality of raw cow’s milk sold in Zongo in the commune of Cotonou (Benin). After taking samples of raw cow’s milk, microbiological analyzes were carried out in the laboratory in accordance with Good Hygienic Practices (BPH). The results of these microbiological analyzes revealed the presence at high loads and therefore, outside the norm of certain microorganisms such as total mesophilic aerobic flora, enterobacteria, thermotolerant coliforms, coagulase positive staphylococci, E. coli and yeasts and molds. Thus, for proper monitoring of hygiene rules, a quality control system must be put in place to allow the population to enjoy good health by consuming good quality raw cow’s milk.
Keywords: Raw milk; microbiological quality; Cotonou; Benin; BPH